Standing room only [compact disc] - McGraw, Tim (Big Machine, 2023)
Three-time Grammy winner and superstar Tim McGraw releases his 17th album, which takes its name from his new hit single. McGraw has sold more than 89 million records worldwide, has dominated the charts with 46 #1 singles, and is the most-played country artist since his debut in 1992.